Democratic Leadership Strategy of KH.Salahudin Wahid in Improving Modern Islamic Education at Tebuireng Islamic Boarding School - Saefrudin, Saefrudin (MODELING: Jurnal Program Studi PGMI, 2025)
K.H. Salahuddin Wahid is a national figure with a background in Architecture education, he is called a technocrat because of his role in physical development at Tebuireng Islamic Boarding School Jombang. This study discusses the figure of K.H. Salahuddin Wahid. three focuses Democratic Leadership Profile of K.H. Salahuddin Wahid in Improving Modern Islamic Education at Tebuireng Islamic Boarding School Jombang. Democratic Leadership of K.H. Salahuddin Wahid in Improving Modern Islamic Education at Tebuireng Islamic Boarding School Jombang. The Role of Democratic Leadership K.H. Salahuddin Wahid dedicates the development of modern Islamic education at Tebuireng Islamic Boarding School, Indonesia. Using a qualitative approach with historical methods, data were collected through interviews, observations, and document analysis. The results of this study indicate that, the profile of KH. Salahudin Wahid shows good democratic leadership Jcharacteristics, including moderate influence, inspiring motivation, intellectual, and collective consideration. His leadership strategy integrates Islamic and general education. Tebuireng Islamic Boarding School has undergone changes in the era of the caretaker K.H. Salahuddin Wahid., Through his role, Tebuireng Islamic Boarding School has undergone changes in physical and non-physical aspects. and the construction of new buildings to support facilities. In the non-physical field, K.H. Salahuddin Wahid established many units to support the process of organizing Islamic boarding schools. The impact is significant, improving the quality of education, modernizing physical facilities, strengthening the role of Islamic boarding schools in society, and expanding alumni networks. This study contributes to understanding how the principles of transformational leadership can be applied effectively in traditional Islamic educational institutions facing modern challenges.